A evasão escolar e a gestão universitária: o caso da Universidade Federal da Paraíba - Fialho, Marillia Gabriella Duarte (2014)
The present thesis aims to study the phenomenon of dropout in higher education and its impacts on the institutional management. Based on the current literature about the theme, it conceptualizes drop out as a macro social phenomenon extensive, international and heterogeneous, which provokes negative impacts on individuals, society and educational management. The literature also pointed out that so far there isn t yet an efficient way to combat this phenomenon. Educational institutions and the society must search for a strategy to minimalize the rates of registered drop out in the education organizations, among of all in the higher education institutions. Based on this information and on statistical data provided by national and international census, the current research is directed specifically to the study of drop out in graduation courses of higher education at the Federal University of Paraíba (UFPB), identifying the manifestations of student s drop out at UFPB in the period from 2007 to 2012 and its impacts on the academic management. The current study can be considered as a type of descriptive research. In order to attempt its objectives, a mixed methods approach (quantitative and qualitative) and different instruments of data collection have been used, such as: interviews with opened and structured questions and audio recording. To carry out the qualitative part of the empirical study a sample of eleven managers from UFPB was selected. Their answers have been analyzed by the content analyses method. For the analyses of the quantitative data there were used descriptive statistical methods, such as: dropout rates, year, investments, and losses. There have been calculated means, percentages, standard deviation and coefficient of variation. The research design assumes the nature of a retrospective longitudinal research. As results of the research, it was possible to identify and classify economic and social losses, highlighted by the managers of the UFPB in the period REUNI . The economic losses of UFPB motivated by the student s dropout are around R$ 415 million causing a negative impact on the university budget. About the social losses, the drop out effectuate that the UFPB is identified as an institution that doesn t fulfill its social role: to form qualified people to contribute with the society and its process of socialization and with the qualification of people for the labor market and the current model of development.